A multifunctional green antibacterial rapid hemostasis composite wound dressing for wound healing. (28th September 2021) - Liang, Wencheng; Lu, Qiaohui; Yu, Fan; Zhang, Junyong; Xiao, Chuang; Dou, Xiaoming; Zhou, Yan; Mo, Xiumei; Li, Jun; Lang, Meidong
Abstract : A green multifunctional wound dressing with low-cost that can accelerate wound healing in comparison to gauze. Abstract : Rapid hemostasis and antibacterial properties are essential for novel wound dressings to promote wound healing. In particular, timely and rapid hemostasis could be of benefit to reduce the mortality caused by excessive bleeding loss. Herein, we present a novel strategy of combining electrospinning technology with post-modification technology to prepare a multifunctional wound dressing, cellulose diacetate-based composite wound dressing (CDCE), with rapid hemostasis and antibacterial activity. It is interesting that the CDCE wound dressing had superhydrophilicity, high water absorption, and strong absorbing capacity, which could eliminate the exudate around the wound in a timely manner and further promote rapid hemostasis. Additionally, its excellent antibacterial properties could inhibit severe infection in the wound and accelerate wound healing. Based on these advantages, the novel CDCE wound dressing could promote wound contraction and further accelerate wound healing compared with the common traditional wound dressing gauze. Taken together, the multifunctional CDCE wound dressing has high potential for clinical application in the future.